Models of mediation and mechanism of its implementation - Podkovenko, Tatyana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article is devoted to the study of the institute of mediation, which has become quite widely used in world and European practice. In resolving conflicts (disputes), mediation provides greater opportunities for the conflicting parties to choose pre-trial and extrajudicial methods to resolve the conflict situation. According to the content of mediation, the role of the mediator, ie an impartial and neutral third party, is primarily to assist the parties in: communicating, identifying their interests and assisting in achieving a mutually acceptable solution. In addition, the tools and techniques are crucial, as well as the style preferred by the mediator. Taking all these factors into account, the doctrine distinguishes many types of mediation, but leaves this catalog open. The article analyzes the main scientific approaches to the classification of mediation models. After many years of using mediation in the common law system, as well as increasing use in the continental law system, there has been a debate about whether mediation is a procedure with clear principles or, as an informal procedure, can take different forms, verified according to a number of elements, for example, cultural, which arise from the specifics of dispute resolution in a particular area, or from kind of the dispute itself. Although the idea of the existence of types of mediation (so-called models or types) was accepted by the world community, it should be noted that the main models of mediation, which are often described in the literature, were formed in North America, Australia and the European Union. It is shown that within one procedure it is possible to distinguish different models, the application of which depends on such elements as: the nature of the dispute, the expectations of the parties, the style of the procedure chosen by the mediator. A professional mediator must have the ability and practical skills to adapt the mediation model to the needs and expectations of the parties. It is emphasized that the existing models of mediation should be considered as a basis for identifying and applying in practice various mediation technologies, which will allow the parties to the conflict to reach an understanding, to find the optimal solution.